Prototyping a measurement device for evaluating the performance of cross-country skis Investigation of pressure-distribution - Kristiansen, P. (University of Oslo, Department of Informatics, 2019)
Cross-country skiing is by many used for recreational purposes. However, cross-country skiing is also a highly competitive Olympic sport. For competitive cross-country skiing, the performance of the skis is of utmost importance. Therefore, much time and energy are spent on tuning and analyzing the mechanical properties of the skis to increase every chance of victory in competitive skiing. In this thesis, we investigate the pressure distribution from the crosscountry skis to the snow. A prototype of a complete mechanical system is developed, using multiple cheap commercially available pressure-sensitive film sensors to measure the force or pressure underneath the ski. We describe the full process of designing a prototype to measure the pressure distribution. From the design of the mechanical system, how we apply a load mimicking the skier to classical cross-country skis, to the analysis of the sensor characteristics and circuit behavior. It was found that the mechanical property pressure distribution could be used to find skis suitable for different weather and snow conditions. This was done by investigating the pressure distribution from two pairs of skis. Cross-country skis suitable for wet snow and warm weather conditions were assumed to have equal pressure zones for both sides of the camber pocket of the ski, with the peak load close to the camber pocket. Also, a shorter contact area for the front section of the ski contributed to the assumptions for warm skis. Cold skis were characterized as more extended contact areas for the front section and a higher peak load in the back section. The calibrations of the sensors had a significant impact on the measurement quality. Due to the combined error from the calibrations and microcontroller unit used, the measurement results proved too inaccurate to draw reliable conclusions on weather classification of skis and twisting in the structure of the ski.